24 A feasibility pilot session: teaching kitchens as innovative nutrition education tool for family medicine residents. (18th October 2022) - Bhat, Shivani; Jain, Rahul; Leung, Rowena; MacAninch, Elaine; Ray, Sumantra; Fleming, Karen
Abstract : Background: The 2006 Canadian Clinical Practice Guidelines on the Management and Prevention of Obesity underscore the importance of nutritional assessment and dietary intervention. Several studies have indicated that medical students receive little education in nutrition. As patients increasingly see physicians as trusted and reliable sources of nutrition information and it is expected that physicians can provide accurate nutrition information. Teaching kitchens have emerged as an education tool and a kind of cooking laboratory that combines culinary instruction using healthful whole ingredients, nutrition education, exercise, mindfulness, and personalized health coaching. Objectives: To investigate the feasibility and efficacy of a teaching kitchen session partnered with a community partner to introduce PGY1/PGY2 Family Medicine Residents of a large Academic Hospital to: i) nutrition counselling for patients; ii) methods to manage personal health and wellness to address burnouts, and iii) nutrition community services for patients. Methods: This study is a participatory intervention pilot consisting of (i) cross-sectional pre- and post-surveys and (ii) a culinary session. The pre-session questionnaire was adapted from the validated NUTCOMP Tool, which measures the self-perceived competence of primary health professionals in providing nutrition care. Open-ended questions were included in the post-session questionnaire to collect data on the experience of the teaching kitchen session. Results: Seven PGY1/PGY2 Family medicine residents attended the 2hr culinary session led by a Registered Dietitian and Community Chef. Residents learned the rationale behind choosing healthy foods to manage hypertension and cooked a 3-course vegetarian meal based on the DASH diet. 83% of the residents were not confident about their nutrition knowledge; 100% of the residents were not or somewhat confident in determining appropriate food goals for patients with CVD; and 82% of the residents were not confident in communicating with their patient about diet modification. All participants found the session enjoyable and would likely participate in a future similar session. All participants identified (1) lack of formal training and (2) time constraints as barriers in providing nutrition counselling in primary care practice. Conclusion: This pilot teaching kitchen session proved to be an engaging, informational and enjoyable way for Family Medicine Residents to engage with community nutrition partners while learning about healthy eating and cooking. Future Culinary Sessions will be developed based on feedback from this pilot study to support Family Physicians and trainees in providing nutrition advice to patients as well as to instill a practice of healthy eating, cooking and wellness.